Hospital Waste Generation and Management in Tertiary Health Care Facilities: A Comparative Assessment. Fako Division, Cameroon - Manga, Veronica Ebot (European Journal of Applied Sciences, 2025)
Wastes generated in hospitals are highly infectious and pose enormous risk to human health and the environment. This study examines the patterns of healthcare waste generation, handling and compliance to legal standards in two tertiary hospitals: public (PU) and private (RT) in Fako Division, Cameroon. Data was collected for a period of two months. Daily waste produced in each hospital was quantified and characterized as hazardous waste (sharps, infectious and pathological or anatomical waste) and non-hazardous or general healthcare waste. Field visits, site observations, interviews and focus group discussions were carried out with selected hospital administrators and workers. A total of 8461kg and 9609kg of waste was generated in PU and RT respecteively. In PU the waste composition was 95.6% and 4.4% for general and hazardous and 42% and 58% respectively in RT. Waste generated per patient was 0.78 and 0.45 kg/patient/day for PU and RT respectively with significant variation (p=0.013) in weekly outputs in RT. Both facilities adopted a four categories waste segregation policy, although no color coding was used. The onsite incinerator in the public hospital was below standard and rarely used whereas that in the private hospital was satisfactory and used regularly. PU engaged the services of a waste provider unlike in RT in which the entire activity was under the hospital administration. Beside the adoption of safer approaches to waste handling and close compliance with regulations in force the study recommends the adoption of sustainable waste strategies contained in the WASH FIT.